De vlam : weekblad voor vrijheid en cultuur. (Amsterdam, 1945)
Bibliotheek Camille Huysmans
Voortzetting van "De Vonk"
Redactie: Wim Storm (hoofdredacteur), Henriette Roland Holst, Richard Jokel, Jef Last, W. Romeyn
Nederlands
Periodiek